A nocturnal cursorial predator attracts flying prey with a visual lure. (April 2015) - Zhang, Shichang; Chen, Hong-Lin; Chen, Kuan-Yu; Huang, Jian-Jun; Chang, Chia-Chen; Piorkowski, Dakota; Liao, Chen-Pan; Tso, I-Min
Abstract : Body coloration has been known to play an important role in animal visual communication. Attraction of prey by visual signals, such as bright body coloration, has been mainly observed in diurnal predators. For nocturnal cursorial predators, however, this foraging tactic has been largely ignored, because one would not expect it to occur under low ambient illumination at night and because of the technical constraints of conducting research in dim light conditions. Metabolic constraints prevent most cursorial spiders moving continuously for a long time to improve prey encounter rate. Any adaptation that induces prey to orient towards these cursorial predators would greatly enhance their foraging success. Bright body coloration of certain nocturnal invertebrates may play such a role. In this study, we investigated colour-mediated prey attraction in a nocturnal cursorial predator, the brown huntsman spider, Heteropoda venatoria, which has a conspicuous moustache-like white stripe on the forehead. We conducted field experiments using dummy and real spiders and monitored with infrared video cameras the responses of nocturnal prey to treatment groups with the white stripe intact or removed. The results showed that in both dummy and real spiders the presence of the white stripe can significantly increase prey attraction rate. Nocturnal flying insects such as moths comprised the majority of attracted prey. We conclude that cursorial invertebrate predators can visually lure prey, especially flying insects such as moths, by their conspicuous body coloration at night. Highlights: Animals use their bright body coloration to lure prey. This strategy has never been found in nocturnal cursorial predators. We examined the prey lure function in a nocturnal wandering spider. Heteropoda venatoria can lure prey with its conspicuous white stripe on the forehead. Nocturnal flying insects are the major prey.